O Sistema Cantareira e a análise de impactos socioambientais da construção da represa do Jaguari-Jacareí, São paulo - Morais, Marta Aparecida de Oliveira (2010)
The current dissertation gathers questions on the issue of the need for construction of dams, their predominant uses and the issue of expropriation, in particular the populations of the Jaguari-Jacarei dike introduced in the Cantareira System, being the last the main supplier of water for the metropolitan region of Sao Paulo. The work was conducted through interviews with families who lived in the area where today is located the huge dam, and with the community who remains near the dike. The paper presents old photos of how the communities were living in the region before the formation of the dam. To conclude, surveys were made of municipal district collection of assets and liabilities, which has grown dramatically after the construction of the dike. The study revealed the existence of negatives and positives socio environmental aspects, resulting from the construction of the dam, which somehow brought many benefits to the municipal district and to the population, due to an increase in tourism which increased revenues amounted to equity, taxes, leisure and jobs growth